Development of Mager Lur Lur Mager Media on Gradient Materials for Junior High School Students - Rosita Ferdiani; Riski Nur Istiqomah Dinnullah (JINoP (Jurnal Inovasi Pembelajaran), 2026)
Background: The low conceptual understanding and student learning outcomes on the topic of gradients of straight-line equations indicate a significant problem in mathematics learning, which may hinder students’ mastery of more advanced mathematical concepts. Objectives: This study aims to develop a valid, practical, and effective learning media called Mager Lur to facilitate students in understanding the basic concepts of gradients in straight-line equations. Methods: This study employed a Research and Development (R&D) method using the 4D development model, consisting of define, design, develop, and disseminate stages. The research involved 36 students from class VIII A and VIII B at MTs Badrussalam, Indonesia. The instruments used included validation questionnaires from media experts, material experts, and practitioners, student response questionnaires, and pretest-posttest assessments to measure learning outcomes. Results: The findings indicate that the developed Mager Lur media achieved a very valid category, with validation scores of 98.50% from media experts, 89% from material experts, and 93% from practitioners. The practicality level of the media reached 80%, categorized as very practical. In terms of effectiveness, the media showed a moderate improvement with an average gain score of 0.57 (57%), indicating that it is quite effective in improving student learning outcomes. Conclusions: The Mager Lur learning media is proven to be valid, practical, and sufficiently effective for use in learning gradient concepts of straight-line equations. Therefore, it can be recommended as an innovative instructional medium to enhance students’ conceptual understanding and learning outcomes in mathematics.